Exploring the Associations Between Systematic Engagement in Physical Activity, Dietary Habits and Body Composition in a Sample of Greek Adolescents - Anastasios Karaoglou; Tzortzis Nomikos; Ioanna Kontele; Tonia Vassilakou; Panagiotis Vlachos; Theodosia Chatzopoulou; Konstantinos Kotrokois (Adolescents)
(1) Background: Adolescence is a critical period in human life, particularly in relation to the development of a healthy lifestyle. Physical activity, body composition and adherence to healthy dietary patterns are key indicators for preventing adolescent overweight and obesity. The aim of this study is to explore the associations between systematic engagement in physical activity, dietary habits and body composition in a sample of Greek adolescents. (2) Methods: In this cross-sectional study, 292 adolescent volunteers, aged 12 to 18 years, from high schools in the Attica region (169 boys [57.9%] and 123 girls [42.1%]) participated. The participants’ socio-demographic characteristics and physical activity levels were assessed through self-reported questionnaires. Their dietary habits were evaluated using the KIDMED questionnaire, and their body composition was determined via bioelectrical impedance analysis. (3) Results: The majority of the students (80.8%) was involved in organized exercise, either as part of a team or in individual sports activities. Physically active participants had significantly improved body composition profiles compared to their non-active peers. No significant differences were observed in the KIDMED scores between boys and girls. However, significantly higher KIDMED scores were found in the group of physically active adolescents compared to the non-active group, with this difference being more pronounced among boys. (4) Conclusions: Engagement in organized physical activity is associated with healthier dietary choices, contributing to a more favorable overall lifestyle profile among adolescents.